ANALISIS PENGELUARAN KONSUMSI PANGAN RUMAH TANGGA DI SUMATERA BARAT - Mayuri, Kiki Neksandi; Gusriati; Herda Gusvita (Fakultas Pertanian, Universitas Ekasakti, 2021)
The purpose of this study was to determine household food consumption expenditure in West Sumatra and to analyze household income, non-food consumption expenditure, and population influencing household food consumption expenditure in West Sumatra. This study uses secondary data from BPS West Sumatra in figures from 1998-2017. The data were processed using multiple linear regression analysis tools with the SPSS 25 program. The results showed that household food consumption expenditure in West Sumatra in the last twenty years, namely 1998-2017, has increased by 4.15%, with an average per year of 0,21%. Household income, non-food consumption expenditure and total population simultaneously (together) have a significant effect on household food consumption expenditure in West Sumatra with value (sig 0,000 <α 0.05). Then the partially significant influence is household income, non-food consumption expenditure, and population. The coefficient of determination is 0.985 (98.5%).